Factors Associated with Premarital Sexual Behavior Among Adolescents in Lhokseumawe City - Juwita Maulani; Fitrayani Fitrayani; Hernita Hernita; Bukhari Bukhari (International Journal Of Health Science, 2025)
Free sexual behavior among teenagers is increasing in Lhokseumawe and triggering various social and health impacts. This study aims to analyze the factors associated with free sexual behavior quantitatively. This study uses an analytical design with a cross-sectional approach. A sample of 100 adolescents aged 15–19 years was selected using stratified random sampling. Data were collected using a structured questionnaire that had been tested for validity and reliability. Analysis used chi-square tests and logistic regression. A significant relationship was found between knowledge (p = 0.002), social media use (p = 0.000), peer influence (p = 0.001), parental role (p = 0.005), and religiosity level (p = 0.000) with promiscuous behavior. The most influential dominant factor is social media usage (OR=4.25; CI 95%: 2.1–8.6). Free sexual behavior among adolescents is influenced by various factors, with social media being the dominant factor. Family, school, and religious-based interventions are needed.